Practical implementation of a full-stack information technology application innovation industry-compliant email system - HUANG Jianbo; SU Xuanrui; LIU Zhiquan (Tongxin xuebao)
Amid the evolving international landscape and the ongoing development of information technology in China, coupled with the increasing challenges to information security, self-reliance and control have become critical indicators and directions for the development of information systems. The email system, a typical information system, operates on hardware, platform software, middleware, databases, and application systems, and includes various services such as Web, POP/IMAP, and SMTP. In the context of the national initiative to promote the localization of information technology, South China University of Technology has actively responded to policy directives, successfully completing the upgrade and transformation of a full-stack information technology application innovation (ITAI) industry-compliant email system, this achievement marks the university as the first in the education sector to implement a fully domestically produced email system. By adopting domestically produced hardware and software, the ITAI-compliant email system ensures security and stability, thereby enhancing the protection of the nation's critical information infrastructure. Took the ITAI-compliant email system deployed by South China University of Technology as a case study, the necessity and feasibility of ITAI implementation was explored.